Agroecological zones [Atlas of African agriculture research and development] - Sebastian, Kate (International Food Policy Research Institute, 2014)
Agroecological zones (AEZs) are geographical areas exhibiting similar climatic conditions that determine their ability to support rainfed agriculture. At a regional scale, AEZs are influenced by latitude, elevation, and temperature, as well as seasonality, and rainfall amounts and distribution during the growing season. The resulting AEZ classifications for Africa have three dimensions: major climate (tropical or subtropical conditions), elevation (warmer lowland or cooler upland production areas), and water availability (ranging from arid zones with less than 70 growing days per year to humid zones where moisture is usually sufficient to support crop growth for at least nine months per year) (Fischer et al. 2009).